Strengthening peace education through interethnical relations in the children's communication forum of batulayang village - Emi Tipuk Lestari; Saiful Bahri; Yulita Dewi Purmintasari; Emusti Rifasinta; Swarnii Swarnii (Peneliti Teknologi Teknik Indonesia, 2021)
Common problems experienced by partners are still found to be negative stereotypes of certain ethnicities and religions. Therefore, the solution that we offer in this service program is to carry out strengthening peace education through inter-ethnic relations. Implementation of Submission of material in the form of a group discussion forum (FGD) about the importance of peace education programs through inter-ethnic relations at the Children's Communication Forum. The purpose of this PKM is so that the younger generation is equipped with multicultural values in order to create an attitude of integration so that it is not easy to be carried away by SARA issues which are very vulnerable to occur in multicultural societies such as in Batulayang. This service has proven to be able to increase understanding of the importance of peace education for the younger generation in Batulayang village. The strengthening of Peace Education is carried out in order to prevent social problems in the form of negative stereotypes between good ethnic groups. This program also institutionalizes social values to citizens so that they have awareness of the risks of any social problems. This PKM also provides citizens with knowledge and skills so as to increase their social intelligence and to increase citizen participation in preventing and overcoming social problems which in the end citizens develop character and character to have responsibility in social life, namely not to riot, violence and brawls, conflicts with other ethnic groups, races and religions, intolerance and human rights violations.